DEVELOPMENT OF A DISCOVERY LEARNING E-MODULE ASSISTED BY PHET SIMULATION FOR SOUND WAVE MATERIAL - Sabaruddin, Sabaruddin; Hafni, Fauriza; Fitriyawany, Fitriyawany (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
This research is motivated by the use of teaching materials that are not varied, and the discussion of physics material is considered difficult due to students' lack of critical thinking. This resulted in students having difficulty understanding the concepts and equations contained in the sound wave material, thus requiring an appropriate learning model, namely discovery learning, where students are expected to overcome the problems faced. So, the development of e-modules based on discovery learning was assisted by Physics Education Technology (PhET) Simulation as a substitute for actual practicum. This study aims to determine the design, feasibility, and practicality of discovery learning-based physics learning e-modules assisted by PhET Simulation on sound wave material. The Alessi and Trollip development model guides an e-module based on discovery learning assisted by PhET Simulation because it is suitable for use in this research model. The resulting product is in electronic form and has three stages, namely: (1) Planning, (2) Design, and (3) Development. The product produced from this research is a learning e-module. Based on the alpha test of media and material experts with a very feasible category of 94.09% and based on the beta test getting a value of 93.92% very feasible category. So, e-modules based on discovery learning assisted by PhET Simulation can be used as physics learning materials on sound wave material, this e-module product can accelerate and clarify abstract theories on sound wave material for students' understanding. The study refers to one material in physics lessons at school, the object of research is still lacking, in the future it can expand the study on other physics materials and expand or increase data for beta testing by manipulating other research variables.